Association Between Saccular Function and Gait Speed. Issue 2 (February 2015) - Layman, Andrew J.; Li, Carol; Simonsick, Eleanor; Ferrucci, Luigi; Carey, John P.; Agrawal, Yuri
<x xml:space="preserve">Abstract</x> Objective To investigate whether otolith function (saccular and utricular) is associated with walking performance. Study Design Cross-sectional analysis of observational data collected in the Baltimore Longitudinal Study of Aging. Setting National Institute on Aging Intramural Research Program Clinical Research Unit at Harbor Hospital, Baltimore, Maryland. Patients Community-dwelling participants. Intervention(s) Cervical and ocular vestibular evoked myogenic potentials (VEMPs) were used to assess saccular and utricular function, respectively. Main outcome measure(s) Cervical and ocular VEMP latency and amplitude responses and usual, rapid, and narrow (20 cm) gait speed assessed over a 6-m course. Results In 314 participants (mean age, 73.1 yr; range, 26–96 yr), cervical VEMP amplitude mediated the association between age and gait speed—particularly narrow walk speed—in both men and women. Cervical VEMP latency had an independent association with gait speed in age-, height-, and weight-adjusted analyses, although the direction of the association differed by sex. Greater cervical VEMP latency was associated with slower usual, rapid, and narrow gait speed in women but faster rapid gait speed in men. Neither the amplitude nor latency of ocular VEMP was associated with gait speed in men or women. Conclusion These findings suggest that age-related slowing of gait speed is in part mediated by the decreased magnitude of saccular response associated with age. The sex-related differential association between saccular response latency and gait speed requires further study.